Role of Mosquitoes, Culex pipiens Complex, in West Nile Fever Virus Persistence in Urbanized Biocoenoses of Saratov - A. M. Porshakov; S. A. Yakovlev; K. S. Zakharov; A. N. Matrosov; T. V. Knyazeva; A. A. Kuznetsov; V. N. Chekashov; M. M. Shilov; S. I. Tolokonnikova; E. V. Kazorina; T. Yu. Krasovskaya; E. V. Naidenova; et al. (Проблемы особо опасных инфекций, 2014)
. In wiggler samples as well as in imago ones detected are WNF virus markers, which indicate the possibility of transovarial and trans-phase transmission of virus into mosquito populations, habitant in urbanized biocoenoses. It is substantiated that Culex pipiens female mosquitoes, which reproduce autogenically, provide for the persistence of the virus within the inter-epidemic period. Therewith there is a possibility of sustained, epidemically-active WNF micro-foci to be formed in the residential area landscapes, and this issue should be given proper consideration when performing assessment of the risks associated with urban population exposure to the infection.